2016
DOI: 10.2135/cropsci2014.07.0468
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alleles Conferring Resistance to Gray Leaf Spot in Maize Derived from its Wild Progenitor Species Teosinte

Abstract: Gray leaf spot (GLS; causal agent Cercospora zeae‐maydis and Cercospora zeina) is an important maize (Zea mays L.) disease in the United States. Current control methods for GLS include using resistant cultivars, crop rotation, chemical applications, and conventional tillage to reduce inoculum levels. Teosinte (Z. mays subsp. parviglumis) is the wild progenitor of maize and easily forms hybrids with current maize inbreds. The aims of this study were to identify alleles from teosinte that, when introduced into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 35 publications
2
44
4
Order By: Relevance
“…Gevers and Lake (1994) identified a GLSresistance allele in a line derived from two teosintes (Z. mays subsp. Soybean leaf blight resistance may be a case in point since, in contrast to our GLS resistance study (Lennon et al, 2015), we have no evidence that the alleles identified in this study are superior to or distinct from resistance alleles that were previously identified in cultivated maize. Maize breeders and plant breeders in general are often reluctant to introduce sources of exotic germplasm into their programs since, as well as a few valuable alleles, many deleterious alleles may be introduced.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Gevers and Lake (1994) identified a GLSresistance allele in a line derived from two teosintes (Z. mays subsp. Soybean leaf blight resistance may be a case in point since, in contrast to our GLS resistance study (Lennon et al, 2015), we have no evidence that the alleles identified in this study are superior to or distinct from resistance alleles that were previously identified in cultivated maize. Maize breeders and plant breeders in general are often reluctant to introduce sources of exotic germplasm into their programs since, as well as a few valuable alleles, many deleterious alleles may be introduced.…”
Section: Discussioncontrasting
confidence: 97%
“…Of the six DTA-QTLs identified in this study, two of them, those on chromosome 8 and 10, were also found as DTA-QTL in our previous study which assessed the same populations for GLS resistance (Lennon et. al., 2015).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…() constructed an F 2 population with Y32 × Ye478 and detected QTLs on chromosomes 2, 3, 4, 5, and 8 that were related to GLS resistance and explained 2.9%‐19.9% of the phenotypic variation. Lennon, Krakowsky, Goodman, Flint‐Garcia, and Balint‐Kurti () obtained RILs by hybridizing teosinte with B73 for resistance QTL mapping and found that resistance genes were located in bins 2.04, 3.06, 4.07, 5.03, 8.06, and 9.03. Mammadov et al.…”
Section: Introductionmentioning
confidence: 99%